Private sector partnership increased adoption of Aflasafe, reducing aflatoxin accumulation and improving net incomes for smallholders in Nigeria - CGIAR Research Program on Agriculture for Nutrition and Health (2019)
Impact evaluation of an IITA-implemented project found that the project created a niche premium market for Aflasafe-treated (AT) maize in Nigeria. The AgResults project incentivized private agribusinesses to work with smallholder farmers to adopt Aflasafe. The project stimulated exponential Aflasafe uptake and increased each smallholder’s net income from maize by $318 and use of AT maize as food by 13%. The main limitation to creation of a larger market for AT maize was awareness of aflatoxin and its health risks.